A New Nitronyl‐Nitroxide Ligand for Designing Binuclear LnIII Complexes: Syntheses, Crystal Structures, Magnetic and EPR Studies. Issue 16 (16th May 2022) - Răducă, Mihai; Martins, Daniel O. T. A.; Spinu, Cristian A.; Hillebrand, Mihaela; Tuna, Floriana; Ionita, Gabriela; Mădălan, Augustin M.; Lecourt, Constance; Sutter, Jean‐Pascal; Andruh, Marius
Abstract: A new nitronyl‐nitroxide ligand (H2 L) featuring alcoholic and phenolic groups has been synthesised starting from 2‐hydroxy‐3‐(hydroxymethyl)‐5‐methylbenzaldehyde (A ). Using this ligand, three 2p–4 f binuclear complexes have been obtained and crystallographically characterized: [Ln2 (HL)2 (hfac)4 ], (Ln=Gd 1, Tb 2, Dy 3 ). Apart from the desired compounds, two by‐products have been isolated as a molecular alloy containing an intermediate bearing hydroxylamino and N‐oxide groups, i. e. (1‐hydroxy‐2‐(2‐hydroxy‐3‐(hydroxymethyl)‐5‐methylphenyl)‐4, 4, 5, 5‐tetramethyl‐4, 5‐dihydro‐1H‐imidazole 3‐oxide, B, and the imino‐nitroxide derivative, C . This system was characterized by single crystal X‐ray diffraction, UV‐VIS and EPR spectroscopy. During the synthesis of compounds 1–3, two other complexes have been obtained and characterized: [Ln(C )(hfac)3 ] (4, Ln=Tb) and [Ln2 (A− H)2 (hfac)4 ] (5, Ln=Tb), where (A− H) results from the deprotonation of the phenolic group in A . The synthetic procedure was optimized in order to obtain pure 1–3 complexes. The cryomagnetic properties of compounds 1–3 have been investigated. Continuous‐wave (CW) electron paramagnetic resonance (EPR) measurements were carried out at X‐ and Q‐band for compound 1 . Time‐dependent experiments were performed at three magnetic fields. Phase memory times, T m, were found to be about 1000 ns at 6 K. Abstract : A new two‐pocket nitronyl‐nitroxide ligand and its binuclear lanthanide complexes have been successfully synthesised and structurally characterized. Their magnetic properties and the EPR spectra are discussed. An interesting case of molecular alloy is formed by two intermediates resulted during the synthesis of the nitronyl‐nitroxide ligand.